MAGIC NUMBERS: SUPPLEMENT, DESCRIPTION AND CLASSIFICATION - Bezdenezhnyi, V. P. (Одеські астрономічні публікації, 2017)
New magic numbers are added to the early known ones, two sequences (large and small) are distinguished which are described in recurrent formulas (1) and (2). Due to the increase of magic number quantity some of the nuclear isotopes which were not considered to be magic have been attributed to such ones. As to isotopes C(6,6), Ca(20,20), Si(14,14), Ni(28,28) and Zr(40,50) they have been referred to twice magic ones. This enabled us to qualitatively explain all the peaks in the curve of isotope abundance. Small twice peaks at magic numbers of neutrons 28, 40, 70, 112 have been added to twice peaks of r-, s- processes of neutron capture at magic numbers 50, 82, 126. Three areas of relative stability at close twice magic isotopes X(112,168), Y(126,184), Z(168,258) and (or) Z’(168,240) are predicted.